Computational fluid-structure interaction : methods and applications - Bazilevs, Yuri.; Takizawa, Kenji; Tezduyar, Tayfun E. (Chichester : John Wiley & Sons, 2013)
'Computational Fluid-Structure Interaction is a complete, self-contained reference that takes the reader from the fundamentals of computational fluid and solid mechanics all the way to the state-of-the-art in CFSI research'--
Includes bibliographical references (pages 353-371) and index.
Keywords: Fluid-structure interaction -- Data processing; Fluid-structure interaction -- Mathematical models